The CIO's Balancing act, Leading Digital Change By Developing Social Skills - Klaus Neundlinger; Sascha Vogel; Simone Rack; Jeanny Gucher (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Our paper is based on the qualitative content analysis (Gläser/Laudel 2010) of expert interviews with IT managers in German speaking countries. Drawing also from organisational development processes we have been carrying out, we analyse how the tension between the service function of IT as specialized unit and its core function regarding digitalization's disruptive impact is balanced. In organisational routines IT often is limited to an ancillary unit and IT management is not involved in strategic decisions regarding core business development. Conversely, IT specialists often are incapable of communicating the opportunities and risks of technological evolution to other business units (Arnitz 2017). Lacking mutual comprehension may cause a loss in terms of trust, cooperation competence and collective learning processes (Fuchs 2005, De Jong 2010), thus risking to hamper organisational change towards an effective use of digital technologies. According to field theory, social skills are sense-making competences that shape strategic action (Fligstein/McAdam 2011). Evidence from interviews and development processes suggests that within the organisational field the CIO can take over the function of a node and starting point for the evolution and diffusion of such social skills. Thus, the CIO's balancing act can be described, on the one hand, as the necessity of taking over a challenger's position within the action field of an organisation's core business in order to promote strategic change in the digital era. On the other hand, this position taking (Bourdieu/Wacquant 1991) has to be reconciled with the necessity of contributing to the transformation of social skills into an organisation's social capital (Badura et al. 2013, Karahanna/Preston 2013), i.e. the capacity of leading internal cultural change in terms of enhancing cooperation, knowledge exchange and innovation.
Keywords: 650; Digital Change; Cultural change; Organisational development; Social skills; Field theory